Urban hikes Washington : a guide to the state's greatest urban hiking adventures - Fralic, Brandon; Wood, Rachel (FalconGuides, 2020)
Explore Washington's lush forests and Cascade Mountain views without traveling deep into the backcountry. This book features 40 easy-to-follow urban trails that allow hikers of all levels to discover the landmarks that shape the Evergreen state's cities and towns.